(untitled) (Perner’s Contacts, 2017)
The contribution briefly presents analysis of payment definitions for the access to the railway infrastructure in Slovak Republic and in chosen countries of EU and consequently it suggests payment definitions for long-term track occupation by railway vehicles on ŽSR network..